EVALUACIÓN DE LAS CARACTERÍSTICAS SENSORIALES DE UNA BARRA DE CHOCOLATE SEMIAMARGO CON TROZOS DE MAMEY DE CARTAGENA (Mammea americana) DESHIDRATADOS - Simi Cerna, Jean Carlos (2023)
The objective of this research project was to evaluate the sensory characteristics of a semi-bitter chocolate bar with pieces of dehydrated Cartagena mamey (Mammea americana), the percentage of national cocoa (CN) and the percentage of Cartagena mamey (MC) were studied, establishing a completely randomized design with nine treatments and three repetitions, the elaboration of chocolate bars was carried out using national fine aroma cocoa as raw material, Each manufacturing process was carried out based on the flow chart defined for the elaboration of the bars, at the end the product was subjected to different tests that allowed determining parameters that the product has, in the physical-chemical analysis ash, moisture, fats and proteins were evaluated.